ENFORCEMENT OF CRIMINAL LAW AGAINST IMPLEMENTERS OF FOREST BURNING - Hayatuddin, Khalisa; Saputra, Leoman (Universitas Islam Negeri Raden Fatah Palembang, 2021)
The background in this study is the rise of cases of forest fires due to the element of deliberate humanity who deliberately burned the forest for personal interests to open new land in Kayuagung District, Ogan Komering Ilir Regency. The formulation of the problem in this study are 1) How is criminal law enforcement against the perpetrators of forest fires in Celikah Village, Kayuagung District, Ogan Komering Ilir Regency ?; and 2) What are the obstacles encountered in the enforcement of criminal law against the perpetrators of forest fires in Celikah Village, Kayuagung District, Ogan Komering Ilir Regency ?. The research method used is empirical research. Data sources used in this study consisted of primary data and secondary data. Based on the results of the study showed that 1) Criminal law enforcement against the perpetrators of forest fires in the village of Celikah, Kayuagung District, Ogan Komering Ilir District has gone through a penal effort that is repressive measures of Investigation because the perpetrators threatened with imprisonment in accordance with criminal theory in applying the principle of subsidiarity and in accordance with article 99 paragraph (1) Article 108 jo Article 69 letter h Law of the Republic of Indonesia No. 32 of 2009 concerning Environmental Protection and Management and regulates criminal sanctions alternatively, namely in the form of imprisonment or only fines and 2) Constraints faced by law enforcement agencies in carrying out criminal law enforcement against perpetrators of forest and land burning, namely first, at the level of investigation, constraints faced is the limited budget support for the management of smoke disasters, the tradition of the community opening land by burning, not yet optimized community empowerment to care about smoke disasters, and the limitations of environmental expert witnesses. Second, at the level of the public prosecutor and judge, the obstacles faced are that the police have never been involved at the level of investigation, the lack of certified public guides and judges (expertise) in the field of environment especially forest and land fires, users of tools that are not of Indonesian national standards.